Variability of temperature, rainfall and reference evaporation of catolé do Rocha-PB municipality, semi-arid region of Brazil - Figueredo, Géssica Martins de; Sousa, Caio da Silva; Mesquita, Evandro Franklin de; Mesquita, Francisco de Oliveira; Diniz, José Paulo Costa; Brito Neto, José Félix de; Melo, Alberto Soares de; Rocha, Josinaldo Lopes Araújo (Revista JRG de Estudos Acadêmicos, 2024)
The state of Paraíba, specifically in the alto sertão of Paraíba, is characterized by the spatial and temporal variability of rainfall, of temperature and evapotranspiration, coming from the semi-arid climate that is inserted in the region, and yet, the performance of different meteorological systems. The objective was to quantify the rainfall, temperature and reference evaporation (mm/ month and mm/year) comprised in the experimental period between 2016 to 2020, in the municipality of Catolé do Rocha-PB, in order to determine the history of the rainy and dry season, and thus, minimize agricultural production losses due to environmental factors. The daily rainfall, temperature and reference evaporation data were obtained by means of a rain gauge and the indirect method of the class A tank, respectively. The rainfall (mm year-1) was analyzed by the nonparametric Friedman test, the Conover test and reference evaporation (mm year-1) applied the parametric test of the ANAVA and the test of Tukey HSD. Both parametric and non-parametric tests were analyzed by Real Statistics. Temperature data was compiled from the website (www.inmet.gov.br) in order to control, statically collecting and decision-making in the process of building scientific knowledge regarding meteorological data (climate - Temperature). Were also analyzed pearson's correlation matrices and elementary principal components analysis for the rainfall variables, Eto and Temperature in the studied experimental period. Were also studied the principal component analysis between the years 2016 to 2020 and its significance by the t test. The average reference evaporation between 2016 and 2020 was 2.1 times greater than rainfall. Mean rainfall and reference evaporation in Catolé do Rocha-PB between 2016 and 2020 were 827 mm ano-1 and 1704 mm year-1 and are compatible with historical averages of 800 mm year-1 and 1700 mm year-1, respectively. Inglesa.